ASSESSMENT OF BACTERIAL BIOFILM ON PATIENTS WITH ORTHODONTIC FIXED APPLIANCES FOLLOWING NON OPERATIVE/PREVENTIVE TREATMENTS - Georgiana Macovei; Sorin Andrian; Gianina Iovan; Angela Gheorghe; Irina Nica; Claudiu Topoliceanu; Maria Bolat; Nicoleta Tofan; Simona Stoleriu; Galina Pancu (Romanian Society of Oral Rehabilitation, 2017)
The orthodontic fixed appliances determine increased retention of bacteria associated with increased cariogenic activity and enamel demineralization. The aim of study is to quantify, by ATP luminiscence method the effectiveness of a remineralizing calcium-phosphate-fluoride-based product used to decrease cariogenic activity to patients submitted to orthodontic fixed appliances therapy. Results. Initially, ATP mean values increased from 3818.3 to 7439.2 after 3 weeks of orthodontic therapy; following the non operative treatment with MI Paste Plus, ATP mean value decreased to 3883.0. Conclusions. The use of fixed appliances in orthodontic treatment influences the retention rate and increases the cariogenic activity of the adjacent bacterial biofilm. The remineralizing calcium-phosphate-fluoride-based products can decrease the cariogenic activity of the bacterial biofilm associated to orthodontic braces. ATP bioluminescence technique can be used for the rapid quantification of bacterial levels and for monitoring the oral hygiene and effectiveness of preventive-therapeutic measures during orthodontic therapy.